The Relationship between Amanatul Ummah Islamic Boarding School and Local Community’s Religiosity - Asep Saifuddin Chalim (Lembaga Pengembangan Pendidikan dan Pembelajaran, Universitas Negeri Malang in Collaboration with Asosiasi Pendidik dan Pengembang Pendidikan Indonesia (APPI), 2017)
Many studies conducted by prominent scholars found that Islamic boarding school in Indonesia have been playing its roles not only in religious and education matter but also in the other areas, such as social, economic and environment. This study sought to analyze the impact of the presence of Islamic boarding school on the religiosity of surrounding Muslim communities the object of the study is households who live in seven villages surrounding the Islamic boarding school Amanatul Ummah, Mojokerto regency, East Java Province, Indonesia. To measure the level of Muslim religiosity, the study used the value of the Five Pillars of Islam dimensions based on the 5-point Likert Scale. By comparing the average value of religiosity of each dimension, it can be drawn a conclusion whether there is a significant positive impact or not. The study found that the average value of Muslim religiosity after the presence of an Islamic boarding school is greater than that before. These findings show that the presence of an Islamic boarding school has a significant positive impact on the surrounding Muslim religiosity. Moreover, the study observes that Islamic boarding school has been practicing a moderate way in Islamic religious proselytizing that makes surrounding communities feel comfortable to adapt and change.